Examining the Relationship between Housing Satisfaction and Post-Occupancy Modifications in Owerri Metropolis - Chukwuma-Uchegbu, Miriam (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
This study explores the relationship between housing satisfaction and post-occupancy modifications (POMs) in Owerri Metropolis, Nigeria. Housing satisfaction influences residential stability, yet dissatisfaction often leads to modifications ranging from aesthetic updates to structural changes. Despite the widespread occurrence of POMs, their link to housing dissatisfaction remains underexplored. A survey of 30 residents (27 responses) assessed housing satisfaction and modification patterns. Findings indicate that while most residents (22 of 26) are satisfied with their housing, 69% (18 respondents) have made modifications, primarily aesthetic (15 respondents) and functional (12 respondents), to address design inadequacies. The study underscores the need for flexible housing designs to enhance satisfaction and reduce modification frequency, recommending adaptable features in future developments.